Cyclohexylmethyl Flavonoids Suppress Propagation of Breast Cancer Stem Cells via Downregulation of NANOG - Liao, Wen-Ying (Hindawi Publishing Corporation, 2013)
Breast cancer stem cells (CSCs) are highly tumorigenic and possess the capacity to self-renew. Recent studies indicated that pluripotent gene NANOG involves in regulating self-renewal of breast CSCs, and expression of NANOG is correlated with aggressiveness of poorly differentiated breast cancer. We initially confirmed that breast cancer MCF-7 cells expressed NANOG, and overexpression of NANOG enhanced the tumorigenicity of MCF-7 cells and promoted the self-renewal expansion of CD24(−/low)CD44(+) CSC subpopulation. In contrast, knockdown of NANOG significantly affected the growth of breast CSCs. Utilizing flow cytometry, we identified five cyclohexylmethyl flavonoids that can inhibit propagation of NANOG-positive cells in both breast cancer MCF-7 and MDA-MB231 cells. Among these flavonoids, ugonins J and K were found to be able to induce apoptosis in non-CSC populations and to reduce self-renewal growth of CD24(−/low)CD44(+) CSC population. Treatment with ugonin J significantly reduced the tumorigenicity of MCF-7 cells and efficiently suppressed formation of mammospheres. This suppression was possibly due to p53 activation and NANOG reduction as either addition of p53 inhibitor or overexpression of NANOG can counteract the suppressive effect of ugonin J. We therefore conclude that cyclohexylmethyl flavonoids can possibly be utilized to suppress the propagation of breast CSCs via reduction of NANOG.